Fig freezing in sugar solutions quality, phenolics composition and sensory properties during storage - Levaj, Branka; Pedisić, Sandra; Pelaić, Zdenka; Dragović-Uzelac, Verica; Lončarić, Sanja, prehrambena biotehnologinja; Repajić, Maja (2021)
The effect of fig freezing in sugar solution on fig"s quality and sensory traits as well as phenolic content during storage was examined. Fresh figs were frozen without any treatment (control - CON), in sucrose solution (30%) (SUC) and sucrose solution (30%) with ascorbic acid (2%) (SUCAA), and stored at -18 ⁰C for 210 days. Samples were analyzed every seventy days for pH, total soluble solids (TSS), sugars and phenolics composition, skin and pulp color, and they were sensorially evaluated. According to ANOVA, storage time showed significant impact on more analyzed parameters than freezing conditions. CON and SUC had the highest TSS, what was also sensorially detected. SUCAA was evaluated with the lowest scores for sweetness and typical fig flavor followed by the highest score for off-taste, off-flavor and off-odor. Contrary to TSS, individual sugars and phenolics were the lowest in CON. SUCAA showed the most brightener skin and the reddest pulp measured by colorimeter, and sensorially it obtained the highest scores for skin and pulp color. Storage time caused TSS and pH decrease, what reflected sensorially as a decrease of fig taste and flavor, as well as the appearance of off-taste, off-flavor and off-odor was also observed. Contrary, individual sugars and phenolics showed increase during storage, and the lowest amounts were present in CON. In conclusion, after 140 days all figs noticeably lost their desirable attributes, where CON fig was sensorially the best evaluated and SUCAA gained the lowest scores.
U radu se pratio utjecaj smrzavanja u otopini šećera na kvalitetu, fenolni sastav i senzorska svojstva smokava tijekom skladištenja. Svježe smokve zamrznute su bez tretmana (kontrola - CON), u otopini saharoze (30%) (SUC) te otopini saharoze (30%) s askorbinskom kiselinom (2%) (SUCAA) te su čuvane pri -18 °C 210 dana. Svakih sedamdeset dana u uzorcima je određivan pH, topljiva suha tvar (TST), sastav šećera i fenola, boja pokožice i pulpe te se provodilo senzorsko ocjenjivanje. Analiza podataka (ANOVA) je pokazala da vrijeme skladištenja ima značajan utjecaj na više parametara u usporedbi s uvjetima smrzavanja. CON i SUC uzorci imali su najviši TST, što se odrazilo na višu senzorsku ocjenu. SUCAA uzorak bio je senzorski ocijenjen s najnižom ocjenom za slatkoću i tipičan okus smokve te s najvišom ocjenom stranog okusa, arome i mirisa. Suprotno TST-u, pojedinačni šećeri i fenoli bili su najniži u CON. Najsvjetlija boja pokožice i najveći udio crvene boje u pulpi izmjereni su kolorimetrom za SUCAA, a tom uzorku je i senzorski boja pokožice i pulpe najbolje ocjenjena. Tijekom skladištenja TST i pH su se smanjivali, što se odrazilo na senzorski lošije ocjenjenu aromu i okus na smokvu, kao i pojavu stranog okusa, arome i mirisa u svim uzorcima. Suprotno tome, pojedinačni šećeri i fenoli pokazali su porast tijekom skladištenja, iako su u najnižoj koncentraciji određeni u CON. Zaključno, nakon 140 dana zamjetno su poželjna senzorska svojstva smokava sve manje izražena, pri čemu je CON najbolje ocijenjen, a SUCAA najlošije.
Bibliografija: str. 50-51.
Summary ; Sažetak.
Keywords: Smokva -- Smrzavanje -- Skladištenje -- Kvaliteta -- Saharoza -- Senzorska svojstva